Dual screen-printed electrode modified by gold – palladium binary system for flow-injection amperometric determination of dopamine and ascorbic acid - L.G. Shaidarova; Y.A. Leksina; I.A. Chelnokova; M.A. Il'ina; A.V. Gedmina; H.C. Budnikov (Учёные записки Казанского университета: Серия Естественные науки)
The gold – palladium binary system electrode posited on the surface of screen-printed carbon electrodes exhibits electrocatalytic activity in the oxidation of dopamine and ascorbic acid. The effect is reflected in a decrease of overvoltage and an increase of oxidation current of organic compounds. The possibility of simultaneous voltammetric determination of dopamine and ascorbic acid at dual screen-printed electrode modified by gold – palladium binary system has been established. A method of flow-injection amperometric determination of dopamine and ascorbic acid on this electrode has been introduced. A linear dependence of the response on analytes has been observed in the ranges from 5?10–11 to 5?10–4 M and from 5?10–10 to 5?10–4 M for dopamine and ascorbic acid, respectively.